Planned Urban Expansion, Social Sustainability, and Spatial Inequality: Evidence from Bahria Town, Karachi, Pakistan - Mian Muhammad Ajmal Khan; Asaad Belal Othman; Ayesha Munir (JAMBURA GEO EDUCATION JOURNAL, 2026)
Rapid urban expansion in Pakistan has intensified private-sector involvement in large-scale urban development, reshaping urban spatial structures, land-use patterns, and social relations. Bahria Town Karachi (BTK), one of South Asia’s largest planned private urban developments, exemplifies these transformations. Despite its planned-city narrative and modern infrastructure, BTK has generated significant environmental, social, and spatial sustainability challenges. This study examines BTK from a social and urban geography perspective, focusing on the spatial dynamics of urban expansion, land transformation, and social sustainability. A qualitative research design was employed using thematic analysis of secondary data, including peer-reviewed literature, government and planning documents, Supreme Court judgments, and National Accountability Bureau (NAB) reports. To situate the case within broader Global South urbanization processes, a comparative spatial analysis was conducted with selected large-scale urban projects in Nigeria, China, and Colombia. The findings reveal systematic socio-spatial sustainability issues, including environmental encroachment into protected areas, forced displacement of local communities without adequate consultation or compensation, and governance weaknesses reflected in opaque land acquisition and planning practices. Comparative analysis indicates that similar spatial inequalities and sustainability trade-offs characterize large-scale private urban developments across the Global South. This study contributes to urban and social geography scholarship by demonstrating how planned urban expansion can reproduce spatial inequality and undermine sustainability objectives. The findings also provide important insights for geography education, particularly in teaching urban sustainability, spatial justice, and land-use change in rapidly urbanizing contexts. Future research should incorporate primary spatial data and participatory approaches to further examine governance and sustainability challenges in urban megaprojects.